Damage Control Management in the Polytrauma Patient - Pape, Hans-Christoph; Peitzman, Andrew B.; Rotondo, Michael F.; Giannoudis, Peter V. (Springer International Publishing : Imprint: Springer, 2017)
This book is an unparalleled source of cutting-edge information on every aspect of rescue, trauma management, and fracture care in the polytrauma/multiple injured patient. Damage control surgery is approached logically and systematically by dividing treatment into phases. The common goal of treating life-threatening conditions first, then treating major pelvic and extremity fractures, requires cooperation among all major disciplines and subspecialties involved in the care of polytrauma patients, and the book is accordingly multidisciplinary in nature. It is edited by pioneers in the field and the authors are all acclaimed experts. This second, revised and updated edition of Damage Control Management in the Polytrauma Patient will be invaluable for all clinicians who must weigh life-saving operations against limb-threatening conditions, including emergency personnel, trauma surgeons, orthopaedic traumatologists, and anesthesiologists.
Keywords: Medicine.; Emergency medicine.; Critical care medicine.; Orthopedics.; Surgery.; Traumatology.; elektronické knihy; electronic books